BASIC GLOBAL RESEARCH TRENDS ON CADASTRE: A BIBLIOMETRIC ANALYSIS - Erkhinova Maftuna Lukhmon khizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract. In this article, particularly the global research status of cadastre was evaluated  by  using  bibliometric  analysis.  This  article  is  based  on  the  analysis  of research  topics,  scientific  production,  collaboration  among  countries  and  authors. Furthermore, most cited papers on cadastre research which obtained from database of Scopus during the time period from 2012 to 2023. Land use changes, as a practical and advanced space exploration technology, offered a lot of valuable data about the earth surface for global analysis. This study focuses on analyzing various aspects of research. These include scientific outputs, research directions, source journals, author performance  and  contributions,  the  distribution  of  research  across countries/territories and institutions, collaboration patterns, and temporal trends in keyword usage.